Concentrations of cortisol, thyroid hormones and thyrotropin in Beagle dogs experimentally infected with Babesia rossi - Schoeman, Johan P. (University of Pretoria, 2024)
Dissertation (MMedVet (Med))--University of Pretoria, 2021.